PERANCANGAN SISTEM PEMPROSES TRANSAKSI PENJUALAN SUKU CADANG MESIN OUTBOAT PADA CV. DINAMIKA MARINE - Efrizal (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2021)
The aim of this research is; 1) To find out the Design of Outboat Engine Parts Sales Transaction Processing System on CV. Dinamika Marine, 2) To design a Transaction Processing System for Sales of Outboat Engine Parts on CV. Web-based Marine Dynamics, AND 3) The design that will be built later is a sales transaction prototype that runs on the Windows operating system and does not require an internet connection. In making this model, the researcher compiled a data flow diagram that used a logical data flow diagram to describe the system to be proposed, while the prototype development process used the waterfall method. the results of the research include; 1) This Outboat Engine Spare Parts Sales application makes it easier to process transaction data and stock data based on sales, firstly the old system analysis, a user needs analysis, system feasibility analysis, system design which includes process modeling with DAD as a design tool, data modeling by making table designs, and designing interface designs and built using a web-based programming language with a database created using MySQL, and 2) The level of accuracy of this application in terms of recording transactions and stocks of Outboat Engine Parts can be seen by day, month and certain years so as to reduce the level of human error. This application can handle changes that occur, such as price changes and additional types of goods, these changes can be processed on the sales transaction form. The application is simple, the language used is easy for the user to understand, so it does not require a long time for training in operating this application